Sodium Dodecyl Benzene Sulfonate Modified Layered Double Hydroxides as a Photocatalyst Under Simulated Solar Radiation for Removal of Malachite Green - Chen, C.X.; Hou, Y.C.; Li, B.; Yi, W.Z. (Asian Journal of Chemistry, 2013)
Sodium dodecyl benzene sulfonate modified layered double hydroxides (DBS-modified-LDHs) were prepared by low saturated state of coprecipitation with microwave assisted crystallization. The resulting samples were characterized by XRD, FT-IR, TEM and ICP-OES. The analytical results show that the as-produced DBS-modified-LDHs have good dispersibility while maintaining the structure of LDHs, indicating the use of microwave irradiation to speed up catalyst preparation is feasible. The formula of the DBS-modified-LDHs was calculated to be Mg2.85Al(OH)7.69(CO3)0.46 (DBS)0.089·2.88H2O, which is in agreement with the FT-IR results. After calcination, the resulting sodium dodecyl benzene sulfonate modified layered double oxide (DBS-modified-LDO) was used for the decolourization of malachite green. The effects of malachite green concentration, catalyst loading and light intensity on decolourization efficiency were investigated. The total time required to decolourize malachite green was found to be 7.5 min in the presence of DBS-modified-LDO (20 g L-1) at 70 ºC and irradiated under a light source (8400 Lux). In addition, used DBS-modified-LDO can be regenerated and the photocatalytic efficiency was stable even after 5 cycles without significant loss in decolourization activity. An average decolourization time of 14.3 min can be obtained during the cyclic process. The results suggest that DBS-modified-LDO can be used as a novel and efficient photocatalyst for the decolourization of malachite green.